INCREASING THE CAPABILITIES OF PEKASIRAN VILLAGE MSMEs THROUGH SOCIALIZATION AND TRAINING IN DIGITAL MARKETING CONTENT CREATION AND BUSINESS LICENSING - Mustahidda, Rahmania; Sugiharti; Nugroho, Prihasantyo Siswo; Bhandari, Rahul; Srisuk, Prattana; Rusuli, Muhamad Saufi Che; Rifai, Agus; Andriyanti (Perwira Journal of Community Development, 2023)
Pekasiran Village, Batur District, Banjarnegara Regency has a role in realizing the development of MSMEs in Indonesia. MSMEs in Pekasiran village still need innovation to further improve existing MSMEs. To increase the capabilities of MSMEs, Most MSMEs in Pekasiran village do not have an effective marketing strategy and mastery of digital marketing knowledge is not yet fulfilled due to the lack of socialization regarding this matter. In accordance with the current conditions of MSMEs in Pekasiran village, dedication is carried out to improve the development of MSMEs in Pekasiran village in the form of creating product photo content, packaging, label and branding innovations, as well as marketing strategies for MSMEs using social media and existing marketplaces. The community service program to increase the development of MSMEs has been running smoothly. The main agenda or work programs that were successfully implemented included Socialization Socialization of the use of digital marketing and business licensing in order to increase the capabilities of MSMEs in Pekasiran Village and Continued outreach activities, assistance to MSMEs for packaging innovation in the form of logos and labelling. Creating and tutoring the using of social media and marketplace.